Model faktor kejayaan kritikal pelaksanaan sistem bangunan berindustri di Sumatera Barat - AlZahri, AlZahri (2021)
Indonesia currently sees the Industrialized Building System (IBS) as the answer to the problem of high demand for housing in line with the rapid economic growth in Indonesia. Housing development in Indonesia, especially in West Sumatera, still uses conventional methods that have proven ineffective in overcoming the said problem. Based on experience and field observations, most players in the construction industry in West Sumatra have a relatively limited knowledge and experience related to the implementation of construction projects that adopt the concept of IBS. This has caused the adoption of IBS is left behind in their construction industry. This research was conducted to identity the strengths and weaknesses of IBS implementation in critical factors for successful implementation of IBS. The methodology used in the study covers several key stages starting with an in-depth review of literature to identify the strengths and weaknesses as well as critical factors in implementating IBS. Next, questionnaires were distributed to 201 respondents representing 3 interest groups in the construction industry in West Sumatera. Reliability and validity tests were conducted on the questionnaire analysis in the early stage, then followed by the Factor Analysis, which produces the critical factors that influence the successful implementation of IBS in West Sumatra. As a result, this study has successfully identified 45 Critical Success Factors (CSF) that formed 7 dimensions of Latent Variables. Subsequent data processing involved modeling the relationship between Critical Success Factors and Project Success (Y) using Structural Equation Modeling (SEM) with the Smart-PLS 3.0 application. A total of 8 hypotheses were tested where the results obtained showed that the Project Success Factor (Y) has a strong relationship with Critical Success Factor (CSF) which can be linked with Planning and Management (SFA) and Coordination System (SFC). Meanwhile, Project Success (Y) is strongly influenced by Time (Y2) and Cost (Y3) factors. Findings from this study has introduce a model, which serves as an important reference to stakeholders in the construction industry to enhance successful implementation of IBS in West Sumatra.